CONSIDERATIONS ON AREAL LINGUISTICS IN THE EXAMPLE OF THE DIALECTS OF THE POPULATION OF EASTERN SURKHANDARYA (Scientific journal of the Fergana State University, 2024)
This article examines language not only as a means of expressing thought, but also the position of language in the community, from a sociolinguistic point of view. The researcher, based on real linguistic theories, comparatively studied the population of Tajiks and Uzbeks living in the eastern part of the Surkhandarya region. The study comparatively characterizes the social vocabulary of both Tajiks and Uzbeks. As can be seen from the article, part of the social vocabulary used by the Tajiks of Eastern Surkhandarya is Turkic-Uzbek words. Some of the words used by Uzbeks in these regions are Tajik-Persian words.